The Application of Work Study to the Compilation of a Fair Sheet - Weeks, C. G. McQ. (The International Hydrographic Review, 2015)
In September 1958 Fleet Work Study Team No. 8 was formed, and appointed to work in the Surveying Service of the Royal Navy. The team consisted of three members — a General Service Lieutenant Commander of the Electrical specialization, a Chief Petty Officer, Surveying Recorder 1st Class, and the writer, then an Assistant Surveyor 1st Class. The first task that the team was given was that of investigating the compilation of a fair chart, embracing all the stages from the field work to the submission into Office of the completed sheet. (For full directive see Appendix.) The object of the study was to reduce chartroom work; the present paper describes firstly how a Work Study is carried out, then the chartroom methods which were in use in 1958, and then the new method which was developed from them. Finally the advantages and disadvantages of the new method are discussed and the reasons explained as to why a method which gives a saving in chartroom work of over 50% has yet to be fully adopted.